2020
DOI: 10.1128/jvi.01530-19
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Mutations A286V and T437M in the Nucleoprotein Attenuate H7N9 Viruses in Mice

Abstract: The low-pathogenic H7N9 influenza viruses that emerged in 2013 acquired an insertion of four amino acids in their hemagglutinin cleavage site and thereby became highly pathogenic to chickens in 2017. Previous studies indicated that these highly pathogenic H7N9 viruses are virulent in chickens but have distinct pathotypes in mice. A/chicken/Guangdong/SD098/2017 (CK/SD098) is avirulent, with a 50% mouse lethal dose (MLD50) of >7.5 log10 50% egg infectious dose (EID50), whereas A/chicken/Hunan/S1220/2017 (CK/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 66 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…H7N9 HPAIVs isolated from avian species have low-to-moderate pathogenicity in mice [7], but after replication in mammalian hosts, the H7N9 influenza viruses could easily acquire more mutations--primarily the PB2 627K or PB2 701N mutation--and then become more virulent in mice [6,[22][23][24]. Several other amino acids in PB2, PB1, PA, and NP were reported to affect H7N9 virus replication and virulence in mammalian cells or animals [5,[25][26][27][28][29][30]. The CK/SD010/IM/19 virus is more virulent in mice than other strains in the same genotype, but all of these viruses have conserved amino acids at positions that have been reported to affect the virulence of H7N9 viruses in mammals (S1 Table ), implying that some other unidentified molecular markers may have contributed to the increased virulence of CK/SD010/IM/19.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…H7N9 HPAIVs isolated from avian species have low-to-moderate pathogenicity in mice [7], but after replication in mammalian hosts, the H7N9 influenza viruses could easily acquire more mutations--primarily the PB2 627K or PB2 701N mutation--and then become more virulent in mice [6,[22][23][24]. Several other amino acids in PB2, PB1, PA, and NP were reported to affect H7N9 virus replication and virulence in mammalian cells or animals [5,[25][26][27][28][29][30]. The CK/SD010/IM/19 virus is more virulent in mice than other strains in the same genotype, but all of these viruses have conserved amino acids at positions that have been reported to affect the virulence of H7N9 viruses in mammals (S1 Table ), implying that some other unidentified molecular markers may have contributed to the increased virulence of CK/SD010/IM/19.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…In addition, other mutations in the viral polymerases-PB2 K526R, A588V, or a combination of PB2 482R, 588V, and PA 497R-also contribute to the pathogenicity of H7N9 virus in humans or other mammals (Song et al 2014;Xiao et al 2016;Yamayoshi et al 2018). A recent study by Ma et al (2020) identified two residues, 286A and 437T, in the NP protein as prerequisites for the virulence of H7N9 virus in mammals. The H7N9 viruses also harbored other known pathogenicity signatures, such as N30D and T215A in M1 and P42S in NS1, which have been shown to increase the pathogenicity of H5N1 viruses (Jiao et al 2008;Fan et al 2009).…”
Section: Pathogenesismentioning
confidence: 99%
“…The GBHG/ QH/9/2015(H5N1) virus had 627 K in its PB2, yet its virulence in mice was intermediate. We speculate that some other residues in its genome may have limited its virulence in mice, as observed in the H7N9 virus by Ma et al [23]. The NA stalk and NS deletions (Table 2) have been reported to increase the virulence of H5N1 viruses in mice [19].…”
Section: Discussionmentioning
confidence: 64%